Skrining Gestational Diabetes Mellitus (GDM) pada Wanita Hamil dan Diabetes pada Lansia di Wilayah Getasan - Widodo, Widodo; Riyadi, Ahmad; Widiyanto, S.Y. Didik; Ayuni, Aulia Qurotul (Poltekkes Kemenkes Semarang, 2023)
Type 1 and type 2 diabetes are influenced by genetic and environmental factors causing a decrease in Î² cell function resulting in hyperglycemia. Patients with hyperglycemia are at risk for chronic complications. The elderly have the potential to suffer from diabetes mellitus due to the age factor and the decreased ability of the body's metabolism. Whereas in pregnant women any hyperglycemia is considered gestational diabetes mellitus (GDM), regardless of diabetes occurring before or during the current pregnancy GDM is diabetes diagnosed in the second trimester or later. This study aims to map cases of diabetes and gestational diabetes. This research is a non-experimental study with a survey method approach without intervention that is descriptive analytic research results of 48 people with a total of 14 men and 5 pregnant women out of a total of 34 female respondents. Examination results for supporting examinations obtained the results of 8 glucose samples with levels > 200 mg/dl and those who had diabetes mellitus based on HbA1c examination were 6 people aged 45-65 years and as many as 3 people aged over 65 years. Respondents who had diabetes mellitus were 2 men and 4 women and none of the pregnant women had gestational diabetes. This research has an impact on the people who take part in this activity, one of which is getting education on how to maintain a healthy quality of life in old age and for those who enter the diabetes mellitus screening group, it is continued in the process of care and assistance by the Getasan Health Center.